B isotope variations at variable scales in arc volcanoes: a case study of lavas from Paniri and Toconce, Northern Chile - Ncetani, Sinethemba (Department of Geological Sciences, 2025)
The mountain building process witnessed today at the Andes is a good modern example of oceanic-continental convergence, providing a modern-day analogue that can be used to interpret older converging mountain belts around the world. Paniri (22°03'34”S, 68°13'42”W) a Pleistocene age stratovolcano and Toconce (22°11'17''S, 68°04'43''W) a late Pleistocene-Holocene age stratovolcano form part of the San Pedro-Linzor Volcanic Chain (SPLVC) that extends between 21°53'S 68°23'W and 22°09'S 67°58'W, located within the Altiplano-Puna Volcanic Chain (APVC), in the Central Andes of Northern Chile. Arc magmas have been widely established as good transporters of elements from the subducted oceanic slab in subduction zones. Boron (B) is an ideal geochemical tracer for the hydration of the overlying mantle wedge at subduction zones. The boron isotope composition of magmas is useful in detecting and quantifying the exchange process between the slab and the mantle. This is due to the large boron isotopic difference between the subducting altered oceanic crust and the mantle, and boron showing strong affinity for silicate melts and aqueous fluids. However, there are no investigations of B isotope systematics of all the units of a single stratovolcano. With B isotope data becoming more accessible due to advances in analytical methods, this study is timely in investigating B isotope systematics within volcanic centres and the regional significance. To provide a firm geochemical framework for the interpretation of compositions in these volcanoes, new O isotope data were collected to complement existing data. The new δ18O values at Paniri (7.69-8.82‰) and Toconce (9.63-10.91‰) overlap with available Andean lava δ18O values and are significantly higher than mantle values of 5.5 to 5.9‰. Paniri and Toconce show increasing δ18O values with increasing 87Sr/86Sr ratios (0.7055 0.7094 range over the SPLVC), and this correlation is indicative of magmas with increased contamination of the parent magma progressively towards the centre of the APMB as was previously observed on a regional scale. New whole-rock boron concentrations and isotope (δ11B) values of samples from all 7 eruptive units at Paniri and from all 5 eruptive units at Toconce are presented, a unique boron dataset for stratovolcanoes. Paniri B contents range from 20 to 50(ppm) with δ11B values from -6.11‰ (±0.35‰) to +0.23‰ (±0.33‰), and Toconce B values range from 19.71 to 83.5(ppm) with δ11B from 11.16‰ (±0.36‰) to -5.06‰ (±0.49‰); both overlapping the range of boron values observed within the Andes. The elevated δ11B values relative to the mantle value of approximately -10‰ support the influence of a more 11B-enriched source like the altered oceanic crust (AOC). Between eruptive units: the older units have more depleted δ11B values when compared to the younger eruptive units at both Paniri and Toconce. Within single eruptive units at Toconce (only one sample per unit was accessible at Paniri): distal samples have depleted δ11B values compared to samples recovered more proximal to the volcanic vent. This suggest that first erupted lavas assimilated most of the 11B-depleted crustal material locally available, with lava δ11B compositions trending towards basement granitoids and metasediments δ11B values (-11 ‰ to -5 ‰). With continued eruption, lavas progressively contain more 11B-enriched values reflecting parental magma compositions of mantle wedge plus AOC (+3.4‰). The local, crustal, 11B-depleted component is therefore not abundant and continued assimilation by successive magmas quickly cause local depletion. A previously proposed two-step process leading to regional B variations in the Central Andes was found to agree with localised Paniri and Toconce data: (1) 11B-rich AOC-derived fluids are mixed with a MORB-like mantle wedge resulting in parental melts of arc magmas with high δ11B values; and, (2) the parental magmas now enriched in 11B continued to ascend through the thick continental crust and APMB, with ~20-30% crustal assimilation at Paniri and 25-45% at Toconce leading to a decrease of the magma δ11B composition while continuing to increase the 87Sr/86Sr ratios. There is a progressive increase in contamination with geographic location when moving from Paniri at the edges of the APMB to Toconce which is closer to the centre of the APMB. This proposed process model agrees with the independently determined degrees of assimilation derived from O-Sr isotope systematics.